Hollowing out national agreements in the NHS? The case of "Improving Working Lives" under a "Turnaround" plan. Issue 2 (13th February 2017) - Roper, Ian; Etherington, David; Lewis, Suzan
Abstract : Purpose: The purpose of this paper is to consider the resilience of a national-level initiative (Improving Working Lives (IWL)) in the face of local-level initiative (Turnaround) in an NHS hospital and compare to Bach and Kessler's (2012) model of public service employment relations. Design/methodology/approach: Case study research consisting of 23 in-depth semi-structured interviews from a range of participants. Findings: The principles behind IWL were almost entirely sacrificed in order to meet the financial objectives of Turnaround. This indicates the primacy of localised upstream performance management initiatives over the national-level downstream employee relations initiatives that form the basis of the NHS' claim to model employer aspiration. Research limitations/implications: The case study was conducted between 2007 and 2009. While the case study falls under previous government regime, the dualised system of national-level agreements combined with localised performance management – and the continued existence of both Turnaround and IWL – makes the results relevant at the time of writing. Originality/value: Some studies (e.g. Skinner et al., 2004) indicated a perception that IWL was not trusted by NHS staff. The present study offers reasons as to why this may be the case.